Total and Partial Substitution of the Local Grass Pea Seed Lathyrus sativa Processed by Different Methods by Soy Bean Meal Glycine max in Small Common Carp Cyprinus carpio L. Diets - Al-asha’ab, Mohannad H; Fadhil, Ali A; Almashhadany, Ahmed J; M Mahmood, Adnan; J Jasim , Sadiq; D Mohammad, Soliman (Al-Nahrain Journal of Science, 2017)
This experiment was carried out in the laboratories of fish and animal resource center-agricultural research directorate from 1/3-30/6/2015 to study the possibility of improving the nutritional value of local grass pea seeds Lathyrus sativa (GPS) by degradation of anti-nutritional factor and using it as protein source for common carp Cyprinus carpio L. diets. Three different treatments for GPS meal, fermented, germinated and soaking (GPS) were used as partial or total replacement of soybean meal (SBM) for practical diets of common carp Cyprinus carpoi L. ration. Thirteen experimental diets were formulated, the diets 1, 2 and 3 were used crud GPS without any treatment at the substitute ratio 33%, 66% and 100% of (SBM), the diets 4, 5 and 6 contained fermented GPS at the same substitute ratio. The diets 7, 8 and 9 were germinated GPS at the same substitute ratio. The diets 10, 11 and 12 were soaking GPS at the same substitute ratio and diet 13 for control without GPS. The results showed no significant differences between control treatment (T 13) without GPS and soaking at substitution ratio 33% and 66% (T 10 and T 11), which were significantly differed (P<0.05) with other treatments. Thereby, it is recommended soaking GPS and at substitute 33% and 66% of SBM for common carp diets.